Bacterial nanocellulose production and application: a 10-year overview - Jozala, Angela Faustino (2016)
Production of bacterial nanocellulose (BNC) is becoming increasingly popular owing to its environmentally friendly properties. Based on this benefit of BNC production, researchers have also begun to examine the capacity for cellulose production through microbial hosts. Indeed, several research groups have developed processes for BNC production, and many studies have been published to date, with the goal of developing methods for large-scale production. During BNC bioproduction, the culture medium represents approximately 30 % of the total cost. Therefore, one important and challenging aspect of the fermentation process is identification of a new cost-effective culture medium that can facilitate the production of high yields within short periods of time, thereby improving BNC production and permitting application of BNC in the biotechnological, medical, pharmaceutical, and food industries. In this review, we addressed different aspects of BNC production, including types of fermentation processes and culture media, with the aim of demonstrating the importance of these parameters.